Culm internodal Anatomy of the Tribe Oryzeae (Poaceae) in Thailand - Pirada Sumanon (Science Faculty of Chiang Mai University, 2019)
Culm internodal anatomy of Oryzeae found in Thailand, namely Hygroryza aristata, Leersia hexandra, Oryza meyeriana var. meyeriana and var. granulata, O. minuta, O. ridleyi, O. rufipogon, O. sativa, and Zizania latifolia, was investigated by transverse sectioning using the paraffin method. The general characters found in most taxa were the intercellular cavities, the hollow center of the culm, and the vascular bundles arranged in rings. The sclerenchyma ring was present only in some taxa. A description of culm internodal anatomy is provided for each taxa. In addition, an identification key is presented based on the presence and the arrangement of intercellular cavities, the presence of collapsed cells, the number of parenchyma cell layers in the cortex between the innermost vascular bundle ring and the hollow center, the number of vascular bundle rings, the presence of a sclerenchyma ring, and the number of fiber cell layers in the sclerenchyma ring. However, culm internodal anatomy alone could not be used to distinguish two varieties of O. meyeriana and three species in the O. sativa group (O. minuta, O. rufipogon, and O. sativa).